Environmental Implications of a Stabilization Pond Effluent Released in Paraná River at Ilha Solteira, Brazil: The Quality of Water and Sediment - Pedroso, Douglas P.; Santos, Felipe A.; Jorgetto, Alexandre O.; Queluz, João G. T.; Rocha, Bruno P.; Jorge, Sônia M. A.; Martines, Marco Antonio U.; Castro, Gustavo R. (Orbital: The Electronic Journal of Chemistry, 2015)
Sewage treatment plants in Ilha Solteira City, which consist of stabilization ponds, have been modifying water and sediment characteristics around sewage outfall area. Water quality parameters such as dissolved oxygen (OD) and conductivity were directly influenced by the sewage outfall. OD values were reported before (6.36 mg L-1) and after (2.94 mg L-1) the sewage outfall. Measurement of organic matter content in the sediment showed the same pattern, with values of 1.34% and 4.80% for the SP1 and SP3 samples, respectively. A copper and zinc analysis indicated that metals are being transported through the water column, and SP3 is an important sedimentation zone. The total concentrations reported for copper are 6.48, 26.97, 37.54, 27.12 and 18.55 mg kg-1 for SP1, SP2, SP3, SP4 and SP5, respectively, and the total concentrations for zinc are 11.21, 48.53, 67.41, 58.62 and 24.76 mg kg-1. Bureau Community of Reference (BCR) sequential extraction indicated the following bioavailability order of copper and zinc: SP1 < SP5 < SP4 < SP3 < SP2. At SP2, more than 70% of the copper and zinc is found in bioavailable fractions. Benthic organism’s analysis indicates that the Oligochaetes correlation with organic matter content is related to the decrease in water quality. DOI: http://dx.doi.org/10.17807/orbital.v7i4.777